Original researchDo soluble p55 and p75 TNF- receptor concentrations play a role in women with primary sterility? - Buks, Joanna; Wilczak, Maciej; Rzymski, Paweł; Opala, Tomasz (Archives of Medical Science, 2010)
Introduction: In modern medicine the cause of infertility is believed to be immune mechanism disorders as well as immune over-reactivity. The objective of this thesis is to evaluate the diagnostic usefulness of measuring the concentration of soluble TNF-α receptors p55 and p75 in women with primary infertility. Material and methods: Examination subjects: 41 female patients with primary sterility in the period January-September 2005. The control group consisted of 13 female patients. For identification of soluble receptors’ p55 and p75 TNF-α concentration was used commercial ELISA kits. Quantitative in vitro method of hormone identification in blood serum of plasma (ECLIA) has been used to estimate hormone concentration. Results have been analyzed with Student’s t-test, Wilcoxon’s test, Fisher’s exact test and Spearman’s test. P value < 0.05 was considered significant. Results: There is no significant statistical relation between concentration of soluble p55 and p75 TNF-α receptors and age, BMI index, or length of periods. In the case of soluble p75 TNF-α receptor a statistical correlation with length of period was found (p = 0.004). From the statistical point of view, the most advantageous relation was found in the case of p75 TNF-α soluble receptor and thickness of endometrium (p = 0.007) as well as the correlation of p55/p75 soluble receptors (p = 0.05). The statistical analysis of correlations between TNFR1 and TNFR2 receptors and concentration of hormones FSH, LH, PRL, E2 and testosterone showed no dependence of TNFR1 and TNFR2 receptor concentrations and concentrations of examined hormones. Statistical analysis of relations of TNFR1/TNFR2 receptor concentrations revealed a significant correlation between these receptors and concentration of LH (p = 0.05). Conclusions: The correlation between endometrium thickness, size of dominating vesicle and concentration of LH compared to concentrations of soluble TNF-α receptors p55 and p75 and their ratio might condition the time of survival of the vesicle or lead to excessive expression of its atresion-leading conditions.